DETERMINANTS OF FOREIGN DIRECT INVESTMENT INFLOWS INTO ASEAN COUNTRIES: A GLS ESTIMATION TECHNIQUE APPROACH - Hoang, Chi Cuong; Nguyen, Van Thu; Tran, Thi Nhu Trang (Journal of International Economics and Management, 2018)
In this article, a strongly balanced panel data during 1997-2014 of 10 ASEAN countries and the Generalized Least Squares (GLS) estimation technique have been employed. This is to identify the factors inducing foreign direct investment (FDI) inflows into the area. The estimated results vary across the groups of country members. For the ASEAN 10, the deterministic factors of FDI are the Real GDP Growth, low Inflation, high Trade Openness Ratio, the Improvement of Infrastructure, and the Political Stability. This is consistent with the theoretical model of the determinant of FDI. Unexpectedly, the Exchange Rate Regime and the Labor Productivity have had a negative impact on FDI flows to the region. In addition, the Asian financial crisis 1997 has had a great negative impact on FDI inflows into the area. For the ASEAN 6, the attractive factors of FDI inflows are low Inflation and the Improvement of Infrastructure. The Asian financial crisis 1997 has also had a great negative impact on FDI flows to ASEAN 6 countries. For the ASEAN 4, the Improvement of Infrastructure and the Labor Productivity have strongly induced FDI flows. However, the Exchange Rate Regime has not encouraged FDI flows to the region like the case of ASEAN 6. And, the Asian financial crisis 1997 has not reduced the FDI flows to the four.